2020
DOI: 10.1016/j.cgh.2019.07.060
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Epidemiology of Chronic Liver Disease and Cirrhosis

Abstract: BACKGROUND & AIMS:Accurate estimates for the contemporary burden of chronic liver disease (CLD) are vital for setting clinical, research, and policy priorities. We aimed to review the incidence, prevalence, and mortality of CLD and its resulting complications, including cirrhosis and hepatocellular carcinoma (HCC). METHODS:We reviewed the published literature on the incidence, prevalence, trends of various etiologies of CLD and its resulting complications. In addition, we provided updated data from the Centers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
581
3
29

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 775 publications
(618 citation statements)
references
References 161 publications
(205 reference statements)
5
581
3
29
Order By: Relevance
“…Reducing exposures to these risk factors is logically the most effective way to lower the risk of developing liver cancer, and this was reflected in the most commonly cited reasons for decreasing incidence rates being mass HBV immunization (30-34, 37, 42, 55, 57, 67), controlling HCV transmission (30,39,51,56), and efficacy of antiviral therapies for hepatitis infection (19, 27, 37-39, 56, 57, 62). New anti-HCV treatments widely available in Western countries offer effective cure of HCV even for patients with advanced liver disease and reduce HCC risk by ∼70% (76); however, their potential benefit has been hampered by lack of affordability and insurance coverage among certain population subgroups (73,75,77).…”
Section: Proposed Drivers Of Incidence Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reducing exposures to these risk factors is logically the most effective way to lower the risk of developing liver cancer, and this was reflected in the most commonly cited reasons for decreasing incidence rates being mass HBV immunization (30-34, 37, 42, 55, 57, 67), controlling HCV transmission (30,39,51,56), and efficacy of antiviral therapies for hepatitis infection (19, 27, 37-39, 56, 57, 62). New anti-HCV treatments widely available in Western countries offer effective cure of HCV even for patients with advanced liver disease and reduce HCC risk by ∼70% (76); however, their potential benefit has been hampered by lack of affordability and insurance coverage among certain population subgroups (73,75,77).…”
Section: Proposed Drivers Of Incidence Trendsmentioning
confidence: 99%
“…The latter include screening of high-risk populations (23,31,47,49,(51)(52)(53)61) and ensuring equitable access to curative therapies for HBV/HCV infections among all population subgroups (23,32,37,47,48,52,53,59). However, even if incidence of HCV-related HCC decreases in the future due to improved treatments and better control (75,81), this may be offset by the emerging etiological importance of NAFLD as a key risk factor (77,82). The latter reflects the continuing increase in the global prevalence of obesity (83,84) and diabetes (84,85), two well-established risk factors for NAFLD (86).…”
Section: Proposed Drivers Of Incidence Trendsmentioning
confidence: 99%
“…Hepatocyte injury (1) causes release of damage-associated molecular patterns, DAMPs (2). These DAMPs lead to Kupffer cell activation (3) and consequent release of inflammatory mediators (4). Kupffer cells can also be activated by pathogen-associated molecular patterns (PAMPs) derived from pathogenic bacteria or viruses (2 ).…”
Section: Hypothesis: Activated Hscs Resemble Mesenchymal Stromal Cellmentioning
confidence: 99%
“…It is estimated that approximately two million deaths per year worldwide are due to liver diseases, including cirrhosis, viral hepatitis, and liver cancer [1]. Although accurate incidence, prevalence, and mortality data are not available for a large number of countries, recent reviews have shown that vaccination, screening, and antiviral treatment campaigns have reduced the disease burden in some regions of the world [2,3]. However, increased use of injection drugs and alcohol, changes in diet and life habits, as well as prevalence of obesity and diabetes, tend to further increase the global burden of acute and chronic liver disease.…”
Section: Introductionmentioning
confidence: 99%
“…(6) Unfortunately, published utilities may not accurately represent contemporary persons with cirrhosis. The epidemiology of cirrhosis has shifted, now characterized by aging persons with nonalcoholic fatty liver disease (NAFLD), alcoholrelated disease, or treated hepatitis C. (7) Cost-effectiveness analyses depend on generalizable utilities but continue to use extremely dated values that are often more than 20 years old and derived from patients with viremic hepatitis C, few of whom had decompensated cirrhosis and few of which capture the contribution of specific cirrhosis symptoms. (8)(9)(10)(11) Updated heath-state utilities are therefore needed in order to execute meaningful cost-effectiveness studies that represent contemporary patients.…”
mentioning
confidence: 99%